Brain-derived Neurotrophic Factor (BDNF) Responses to Exercise in Individuals with Spinal Cord Injury: A Systematic Review - Nurhaida Rosley; Hafifi Hisham; Nur Izyan Mohd Amin; Halimatul Saadiah Abd Ghani; Haidzir Manaf; Nor Azlin Mohd Nordin (Asian Journal of Medicine & Health Sciences, 2024)
Introduction: Spinal Cord Injury (SCI) leads to debilitating effects. This study aimed to conduct a systematic review examining the correlation between exercise, physical activity, and levels of Brain-Derived Neurotrophic Factor (BDNF) in individuals with SCI. Method: A search was conducted between 2013 and 2023 using the PubMed, CENTRAL, Medline, and Wiley Online Library databases, along with bibliographic searching. The evaluation process was conducted at each stage to identify eligible studies. Methodological quality assessments were performed on each eligible study, and the data were presented in tabular form. Results: Out of 2,928 papers, only five met the eligibility criteria for inclusion in the review. The methodological quality of the included studies ranged from low to moderate. The demographic variables of the participants, including age, years since injury, gender, level and severity of injury, sample size, study design, intervention, outcome measures, and findings, were organized into a table. All the included studies exhibited heterogeneity. Conclusion: The findings suggest a potential association between exercise and physical activity and BDNF concentration levels in individuals with SCI. However, further research with larger sample sizes and rigorous methodology is necessary to establish the long-term effects of exercise and physical activity on BDNF concentration levels. Clinically, this review underscores the importance of tailored exercise interventions in enhancing neuroplasticity and recovery in SCI patients.